DESAIN MAJALAH LENSA SUCOFINDO - Muhammad Mahesa Bagaskara (Politeknik Negeri Jakarta, 2016)
ABSTRACTPT SUCOFINDO doing creative step and offer innovative new services based on competence. So, in adding to the quality of work of employees, SUCOFINDO make a magazine entitled LENS (Lantern Inspiration) which aims to provide information, appreciation and media make communication between employees as well as employees of the company among employees. In developing LENS magazine, SUCOFINDO have constraints on the magazine, namely, the design layout of the first and second editions inconsistent on the elements and principles of design. So that the third edition will be created a new concept and created a template for the design layout consistent. The selected design is elegant theme, because in accordance with the elements and principles of design that is geared towards clients. From the work of the selected design will be applied to art carton 260gr with laminating for cover and matte art paper 150gr to the page contents. With a size of 210 x 275 mm to 56 pages including cover.Keywords : Magazine, Design, CreativeABSTRAKPT SUCOFINDO melakukan langkah kreatif dan menawarkan inovasi jasa-jasa baru berbasis kompetensinya. Maka, dalam menambah kualitas kerja karyawannya, SUCOFINDO membuat suatu majalah yang berjudul LENSA (Lentera Inspirasi) yang bertujuan untuk memberikan informasi, apresiasi dan menjadikan media komunikasi antara karyawan terhadap perusahaan maupun karyawan antar karyawan. Dalam pengembangan majalah LENSA, SUCOFINDO memiliki kendala pada majalahnya yaitu, desain layout pada edisi pertama dan kedua tidak konsisten pada elemen dan prinsip desainnya.Sehingga pada edisi ketiga akan dibuat konsep baru dan dibuatkan template agar desain layout konsisten. Desain yang terpilih adalah tema elegant, karena sesuai dengan elemen dan prinsip desain yang diarahkan klien. Dari hasil karya desain terpilih akan diaplikasikan pada art carton 260gr dengan laminating doff untuk cover dan art paper 150gr untuk halaman isi. Dengan ukuran 210 x 275 mm sebanyak 56 halaman termasuk cover.Kata Kunci : Majalah, Desain, Kreatif